The effects of integrating the Manchester Pain Management Model and empowerment education on postoperative rehabilitation after cesarean section: A comprehensive intervention study - Jiang, Hailing; Xu, Ronghua; Li, Lingfang; Zhu, Haijuan (PloS one, 2025)
To evaluate the effect of combining the Manchester Pain Management Model (MPMM) with the enabling education model as a comprehensive intervention in maternal rehabilitation after cesarean section. A total of 120 women who underwent cesarean section in our hospital from June 2021 to June 2023 were randomly divided into observation group and control group, with 60 cases in each group. The control group received standard nursing measures, while the observation group received comprehensive nursing measures combined with Manchester pain management and enabling education model. A rigorous randomized controlled trial design was employed. Data were analyzed using independent t-tests for continuous variables and chi-square tests for categorical variables, with a significance level set at P < 0.05. Postoperative pain degree (VAS score), postoperative recovery indicators, and nursing satisfaction scores were compared between the two groups. The pain scores at 4 hours, 12 hours and 24 hours after surgery, the first independent time out of bed activity, the first time to exhaust gas and the length of hospital stay in the observation group were significantly lower than those in the control group (P < 0.05), and the success rate of the first breastfeeding and nursing satisfaction were significantly higher than those in the control group (P < 0.01). The combined intervention of the Manchester pain management model and empowerment education significantly improved postoperative pain control, accelerated physiological recovery, and increased overall satisfaction with nursing care. This model may provide an effective new method for rehabilitation management after clinical cesarean section.